(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article examines the concept of "fear" in Uzbek and English literary discourse using a linguistic-cognitive framework. . Through a comparative analysis of literary works, we identify the main conceptual metaphors and metonymies used to express fear, and study their cultural and linguistic influence. Our findings reveal distinct but interrelated conceptualizations of fear across the two languages and highlight the influence of cultural background on the linguistic expression of this basic human emotion.